Effects of developing ice covers on bridge pier scour. Issue 4 (4th July 2022) - Sirianni, Dario A. B.; Valela, Christopher; Rennie, Colin D.; Nistor, Ioan; Almansour, Husham
Abstract : Current research investigating ice-covered bridge pier scour has focused on the effects of fully developed ice jams. However, based on observations at various stages of development, ice covers are not always fully developed. This experiment investigated pier scour at various stages of a simulated floating ice jam's development, with a constant flow rate. Various channel-spanning ice cover lengths were tested, along with one circular localized cover, and resulting pier scour was compared to free-surface flow pier scour. Five lengths of downstream initiated ice covers were tested, with lengths upstream of the pier being 0, 0.63, 1.33, 2.66 and 5.32 m. The local cover's diameter was 0.27 m, three times the pier diameter. The 2.66-m ice cover produced the greatest scour and near-bed Reynold stress, with greater scour depth and volume, respectively, by 46.9% and 238% compared to free-surface flow conditions, whereas the local cover produced the smallest scour increase.